Fish as a source of acoustic signal measurement in an aquaculture tank: acoustic sensor based time frequency analysis - Hassan, Shahbaz Gul; Ahmed, Shakeel; Iqbal, Shafqat; Elahi, Ehsan; Hassan, Murtaza; Li, Daoliang; Zhou, Zhiyan; Abbas, Adnan; Song, Cancan (International Journal of Agricultural and Biological Engineering, 2019)
Acoustic signals travels rapidly in water without attenuating fish telemetry. The digital sonar and passive acoustic has been used for fish monitoring and fish feeding. However, it is an urgent need to introduce new techniques in order to monitor the growth rate of fish during harvesting and without causing adverse effects to the harvested fish. Therefore, a novel technique was introduced to probe the acoustic signal frequency ratio in absence and presence of the fish in tanks, which basically uses an acoustic sensor (hydrophone), acoustic signal processing system (scope meter), and a signal monitoring system (fluke view). Acoustic signals were selected from 48-52 Hz frequency, measure of dispersion of frequency signal represented as a function of time via Xlstat software. Measure of dispersion displayed a significant effect of acoustic signal in the presence and absence of the fish in tanks. These optimised protocols of this study will help to control and prevent excessive wastage of feed and enhance proper utilization of feed that chiefly enhance fish growth in aquacultureKeywords: acoustic signals, acoustic sensor, fish, aquaculture, time frequency analysis, signal processingDOI: 10.25165/j.ijabe.20191203.4238Citation: Hassan S G, Ahmed S, Iqbal S, Elahi E, Hasan M, Li D L, et al. Fish as a source of acoustic signal measurement in an aquaculture tank: Acoustic sensor based time frequency analysis. Int J Agric & Biol Eng, 2019; 12(3): 110–117.